3D Modeling Technology of Mobile Big Data Application in the Electric Vehicle Condition Monitoring System. (27th August 2022) - Wang, Ziyang; Li, Gangjun
Abstract : In recent years, the modern information society has entered the era of big data. Big data has rapidly developed into a popular category favored by academia and industry and has been widely used. This paper is aimed at studying the application of the 3D modeling technology of mobile big data to the monitoring of the state of electric vehicles. It proposes related concepts of big data algorithm and 3D modeling technology, introduces the trajectory matching algorithm based on mobile big data, and finally introduces the related concepts of electric vehicles and the design of the big data analysis platform for condition monitoring of substation equipment. On the basis of discussing the application of the three-dimensional modeling technology of mobile big data in the electric vehicle condition monitoring system, the experimental research was carried out with the big data in the condition monitoring of the intelligent substation. The experimental results of this paper showed that the storage overhead of the NJLS model was reduced by 34% to 40% compared with the conventional star schema, which could reduce the space overhead.